Circulating cartilage oligomeric matrix protein in juvenile idiopathic arthritis. (4th May 2017) - Lewander, P; Dahle, C; Larsson, B; Wetterö, J; Skogh, T
Abstract : Objectives: Raised serum cartilage oligomeric matrix protein (sCOMP) has been reported to predict erosive disease in early rheumatoid arthritis (RA). In juvenile idiopathic arthritis (JIA), subnormal sCOMP levels have been associated with ongoing inflammation and growth retardation. In this study we aimed to assess sCOMP, C-reactive protein (CRP), and insulin-like growth factor (IGF)-1 in children/adolescents with JIA and in referents. Method: We enrolled 52 JIA patients at planned outpatient visits and 54 inpatients with ongoing infection ('infection referents'). A total of 120 referents testing negative for immunoglobulin (Ig)E-mediated allergy ('IgE referents') served as controls. All serum samples were analysed for COMP, IGF-1, and CRP. Results: The average sCOMP level was highest among the IgE referents and lowest among the infection referents. In the JIA patients, the level of sCOMP was not associated with the level of CRP or with clinical signs of disease activity. Conclusions: The results of this study do not support routine clinical analysis of sCOMP levels in patients with JIA.